Produtividade do feijão-de-corda e acúmulo de sais no solo em função da salinidade da água e da fração de lixiviação - Assis Júnior, José Otacílio de (2007)
The cowpea is a very important crop in the diet of the inferior social classes, but its productivity is very low, especially is non-irrigated areas. However, the irrigation in semi-arid areas has been associated to soil salinization. The study had the objective to evaluate the effect of water salinity and the leaching fraction on the growth and the productivity of grains of cowpea plants (Vigna unguiculata), cv, Epace 10. The experiment was set up in the experimental area of the Laboratório de Hidráulica e Irrigação/UFC, during the dry season. A completely randomized block design, with five repetitions, was adopted. Each experimental unit consisted of 4 lines of plantation of 5.0 m. The treatments studied were